Dynamics of Muscular Performance Indices during the 30‑s Vertical Jump Test in Endurance and Sprint Cohorts - Eugenijus Trinkūnas; Alfonsas Buliuolis; Rita Sadzevičienė; Birutė Zacharienė (Lithuanian Sports University, 2018)
Research background and hypothesis. According the methodological requirement testing procedures do not modify the main training objectives. It is well known that specificity of performance assessment tests is important if we want to compare performance of different groups tested. Research aim was to find out the peculiarities of muscular performance indices in sprint and endurance cohorts while performing a 30-s vertical jump test. Research methods. The participants of the study were two groups of athletes, i. e. sprint and endurance runners. The participants of the study performed a 30-s vertical jumps test with maximal efforts. The sum of height of all jumps was calculated by a special computerized program and the values in height of jumps, contact time and relative power at onset of workload and at each 5 seconds of the test were analyzed. Research results. The difference between the cohorts in jumps height was statistically significant (p < 0.05) during the whole series of jumps. Athletes' adaptation to speed-power type of exercising produced higher anaerobic muscle performance indices while performing 30-s duration jumps test. Endurance runners usually demonstrate lower results in jumping than sprint- athletes and they compensate reduced muscular power with prolonged duration of take-off. Discussion and conclusions. Despite some methodological limitations the results of this study show that the assessment of muscular performance indices allows assessing the peculiarities of dynamics of relative muscle power and fatigue. Keywords: endurance and sprint running, muscular performance, vertical jump test.